Liposuction: An update on one of the most frequently performed and controversial surgeries - Fagan, Frank (Operating Room Nurses Association of Canada Journal, 2001)
Liposuction surgery (which includes suction- assisted lipectomy, lipoplasty, lipolysis, liposculpture as well as the more recently introduced tech- niques - ultrasound-assisted liposuction and power-assisted lipoplasty) has become one of the most frequent major aesthetic surgical procedures performed in the United States (where figures are available) and probably in Canada, according to a recent survey (ASAPS, 1999). This survey, along with a review of a number of current journal articles show that liposuction has come a long way since its introduction in the early 19808 (Illouz, 1983). The medical specialists most commonly associated with liposuction procedures include plastic surgeons, dermatologists, and otolaryngologists.